The abnormal expression of chromosomal region maintenance 1 (CRM1)-survivin axis in ovarian cancer and its related mechanisms regulating proliferation and apoptosis of ovarian cancer cells. Issue 1 (1st January 2022) - Zhang, Jing; Xu, Xinyan; Chen, Yongfeng; Guan, Xiaoju; Zhu, Hong; Qi, Yuhong
ABSTRACT: Ovarian cancer (OC) is the main type of cancer that affects the female reproductive system and has a high morbidity and mortality rate. This study aimed to explore the regulatory effect of the chromosomal region maintenance 1 (CRM1)-survivin axis on the progression of OC. Ovarian cancer cells were transfected with pcDNA3.1-survivin and short hairpin RNA (sh)-CRM1. Cell proliferation was analyzed by cell counting kit-8 (CCK8), 5-ethynyl-2´-deoxyuridine (EdU) staining, and colony formation assays. Apoptosis was detected using flow cytometry. Quantitative real-time polymerase chain reaction (qRT-PCR) and Western blotting were performed to analyze the expression of RNA and protein, respectively. qRT-PCR and prognostic correlation analyses revealed that CRM1 is highly expressed in OC cells and related to survival. The results of qRT-PCR, CCK8, colony formation test, EdU staining, flow cytometry, and Western blotting showed that CRM1 silencing inhibited the proliferation and colony formation of OVCAR 3 and SKOV3 cells and promoted cell apoptosis by promoting Caspase-3 activation. Survivin was positively regulated by CRM1 and promoted the development of OC. The results of the rescue experiment showed that overexpression of survivin reversed the inhibitory effect of CRM1 knockdown on the proliferation of ovarian cancer cells and its inhibitory effect on apoptosis. Our findings confirm the role of the CRM1-survivin signal transduction axis in OC by regulating the proliferation and apoptosis of OC cells, and may thus serve as a potential therapeutic target for OC.